1990
DOI: 10.1002/mpo.2950180411
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile chronic myelocytic leukemia: Experience with intensive combination chemotherapy

Abstract: Six children with juvenile chronic myelocytic leukemia (JCML) with adverse prognostic features were treated with intensive combination chemotherapy similar to that utilized in patients with acute nonlymphocytic leukemia (ANLL). Despite obtaining hematologic remissions after induction therapy, clinical findings of extramedullary disease persisted. The use of intensive post-induction chemotherapy did not erradicate persistent extramedullary disease, and all patients developed hematologic relapse and progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 16 publications
(5 reference statements)
2
17
0
1
Order By: Relevance
“…43 About 50% of children with MDS treated with intensive chemotherapy enter CR, but only 15% to 30% remain in CR. 15,[44][45][46][47] The present study showed a similar CR rate of 60% in Ϫ7 Ϯ other. Among those who entered CR the OS rate was 43%.…”
Section: Discussionsupporting
confidence: 71%
“…43 About 50% of children with MDS treated with intensive chemotherapy enter CR, but only 15% to 30% remain in CR. 15,[44][45][46][47] The present study showed a similar CR rate of 60% in Ϫ7 Ϯ other. Among those who entered CR the OS rate was 43%.…”
Section: Discussionsupporting
confidence: 71%
“…63 ' 64 In the series reported by Castro-Malaspina, 5 no complete remissions were achieved in 38 patients, 33 of whom were treated with conventional chemotherapy. Interestingly however, a dramatic change in the death rate was apparent at 2 years, suggesting that there are two subgroups of patients, the first being the majority of patients whom have a short survival, and the second much smaller group, with a much longer survival.…”
Section: Prognosis and Therapymentioning
confidence: 96%
“…Others have also observed that the aggressive chemotherapy used to treat monosomy 7 associated AML in children and young adults results in survival at best in the range of 15%. 6,15,16 Allogeneic marrow transplantation has been the only potentially curative treatment for adult and pediatric patients with MDS. There are few data regarding the outcome of transplantation for children with various types of MDS.…”
Section: Raeb; Raeb-t; Jmml; Cmmlmentioning
confidence: 99%